Effect of the calcium level and limestone particle size on the performance of semi-heavy layers in the second cycle of egg production - Pizzolante, CC; Garcia, Edivaldo Antonio [UNESP]; Laganá, C; Saldanha, ESPB; Deodato, AP; Faitarone, ABG [UNESP]; Scherer, MR [UNESP]; Batista, L [UNESP] (Fundação APINCO de Ciência e Tecnologia Avícolas, 2006)
An experiment was carried out at the Research and Development Unit of Brotas aiming at evaluating dietary calcium level and limestone particle size on the production performance of commercial (Hy-Line Brown) layers in the second lay cycle. Experiment duration was 112 days. A total number of 288 hens, with 83 weeks of age in the beginning of the experiment, were used in a completely randomized experimental design in a factorial arrangement of 2x3, with two calcium levels (3.5 and 4.0%) and three limestone particle size compositions: 100% fine limestone (FL), 30% coarse limestone (CL) + 70% fine limestone (FL), and 50% (CL) + 50% (FL), with six replicates of eight birds each. Egg weight (g), egg production (%), egg mass (%), feed intake (g), feed conversion ratio (kg/dz and kg/kg), mortality (%), and egg loss (%) were evaluated. The analysis of variance did not detect significant differences (p>0.05) among treatments on any of the evaluated performance parameters. It was concluded that the tested calcium levels and limestone particle composition did not influence the performance of semi-heavy layers in second production cycle.
Keywords: Calcium; laying hens; limestone; particle size; performance